Resignificación de espacios públicos efectivos en zonas residenciales periféricas. (2022)
The main focus of this project is on the space of urban peripheries and, more specifically, on the possibilities of generating transformations of significant public spaces in this type of environment based on community participation processes and specific urban concepts. We opt for a more social than geographical definition of the urban periphery, understanding it as those territorial enclaves that concentrate processes of physical and social degradation as a consequence of the concentration of problems, neglect of public powers, disinterest-marginalization of private capital and in this case , emphasizing the lack of effective public spaces, understood as squares, parks, small squares, etc.